Manajemen Resiko dalam Perubahan Budaya Kerja Perguruan Tinggi Keagamaan Islam Swasta di Lombok - S. Ali Jadid Al Idrus (ISLAMIKA, 2023)
This paper aims to find out the urgency of risk management in the development of private Islamic religious tertiary institutions, to read threats and opportunities, leadership commitment, the contribution of risk management implementation to institutional progress, and to use swot analysis in calculating policies and decisions. This institution has several characteristics in academic, sociological, anthropological and political aspects with internal and external problems in the form of limited human resources, infrastructure and accreditation of institutions and study programs which are still low and a very poor partnership network. Qualitative methods are used to study various phenomena and problems by matching empirical reality with an objective focus, with a case study approach, determining key informants and researchers as key instruments. Primary data collected is directly related to research questions, data obtained through observation, interviews and documentation. Data was collected and then analyzed with an interactive approach. The application of risk management in private Islamic religious tertiary institutions can reduce threats and increase opportunities, establishing program certainty can be a guarantee to the community. Leaders of foundations, Islamic boarding schools and institutions implement risk management to increase public trust in PTKIS in Lombok, as evidenced by the resilience to acculturation and empowerment in the community running effectively. SWOT analysts are able to provide signals to community members to accelerate quality management.